Inflammaging: Expansion of Molecular Phenotype and Role in Age-Associated Female Infertility - Ivanov, Dmitry; Drobintseva, Anna; Rodichkina, Valeriia; Mironova, Ekaterina; Zubareva, Tatyana; Krylova, Yuliya; Morozkina, Svetlana; Marasco, Maria Greta Pia; Mazzoccoli, Gianluigi; Nasyrov, Ruslan; Kvetnoy, Igor (Biomedicines, 2024)
Cellular aging is considered as one of the main factors implicated in female infertility. We evaluated the expression of senescence-associated secretory phenotype (SASP) markers and additional molecular factors in an in vitro model of cellular aging. We induced genotoxic stress (UVB/UVA ray irradiation) in primary human endometrial cells obtained from female subjects of young reproductive age (<35 years of age). We assessed the expression levels of IL-6, IL-8, IL-1α, MMP3, SIRT-1, SIRT-6, TERF-1, and CALR at the mRNA level by RT-qPCR and at the protein level by immunofluorescence and confocal microscopy in primary human endometrial cells upon induction of genotoxic stress and compared them to untreated cells. Statistically significant differences were found for the expression of SIRT-1, SIRT-6, and TERF, which were found to be decreased upon induction of cell senescence through genotoxic stress, while IL-6, IL-8, IL-1α, MMP3, and p16 were found to be increased in senescent cells. We propose that these molecules, in addition to SAS-linked factors, could represent novel markers, and eventually potential therapeutic targets, for the aging-associated dysfunction of the female reproductive system.